Hidden Clues: Unusual Clinical Profiles of Typhoid-Related Intestinal Perforation - Tauqeer Ahmad, Ali Shaheer, Varda Balouch, Durdana Mohsin, Sassi Manzoor Hassan, Tekchand Maheshwari, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Typhoid-related intestinal perforation (TIP) remains a life-threatening complication of typhoid fever, particularly in endemic regions such as South Asia. While classical presentations of TIP are well-documented, atypical clinical features are increasingly observed, complicating timely diagnosis and management. This study aimed to characterize unusual clinical profiles of TIP in a tertiary care hospital in Pakistan. Methods: The study was performed at the General Hospital Lahore between January 3, 2023, and June 30, 2023. Non-probability consecutive sampling was used to include patients aged 12-79 years with confirmed TIP on clinical, radiological, or intraoperative examination. The data regarding demographic characters, symptom duration, fever, and abdominal findings were gathered through a structured proforma. Continuous variables were given in the form of median (IQR), and categorical variables using frequencies and percentages. Chi-square or Fisher exact test were used to conduct the tests of comparisons with P ≤ 0.05 taken as significant. Findings: 41-45 patients were used in the analysis, with an average age of between 22-24 years and male prevalence of 78-84. It is worth noting that 94-98% of them had at least one atypical clinical feature, and 22-25% of them came in with all three complications at the same time. The most common abnormal manifestations were abnormal illness duration (6574%), intermittent fever (5864%), and the lack of classical abdominal rigidity (2835%). Intraoperative observations showed that there were more single (62-69) perforations of the ileum with local purulent contamination (70-78) and that more than 26-33 cases had multiple perforations. Conclusion: Atypical TIP presentations are highly prevalent and contribute to diagnostic delays, potentially increasing morbidity. Recognizing non-classical patterns—including intermittent fever and variable symptom duration—is essential for prompt surgical intervention and improved outcomes in endemic settings. Keywords: Typhoid fever, intestinal perforation, atypical presentation, surgical emergency, South Asia.